Implementasi Kebijakan Tata Kelola Lahan Pemakaman Oleh Dinas Cipta Karya, Bina Konstruksi, Dan Tata Ruang (Studi Kasus Pada UPT Wilayah 1 TPU Cibarunay Kota Bandung) - Al’libani, Ridha Rahim; Ferninda, Muhammad Dimas; Maulana, Ega Syahrul; Fadilah, Mila Nur; Widiawati, Sinta (Neolectura, 2025)
Public cemeteries play a significant role in the community as a place to bury deceased family members. Local governments are responsible for providing this service to meet the community's need for proper burial grounds. The community's perspective on cemeteries is an important consideration for local administrators. The City of Bandung provides various information and services related to public cemeteries. In accordance with Bandung City Regulation No. 5 Article 3 of 2023 on Public Cemetery Services, the local government provides land for public cemeteries. One of the problems encountered in the field is the limited availability of land for cemetery management, which is a factor affecting both administrators and the community. This study aims to examine the implementation of cemetery land management policies, as well as the challenges and efforts undertaken by the Cibarunay Public Cemetery Office in Bandung City. This is a qualitative study using a descriptive case study approach, where the research describes or portrays real-life events in written form. Data collection techniques include interviews, observations, and documentation. In this study, the theory used by the researcher is Charles O. Jones' implementation theory, which includes organization, interpretation, and application. The results of the study show that the implementation of cemetery land management policies at the Cibarunay Public Cemetery Office in Bandung City is running well, but there are still obstacles that occur in the field. In terms of organization, the program is running smoothly, with the TPU office implementing it continuously to maintain public understanding and knowledge. In terms of interpretation, it is progressing appropriately, but internally, the managers staff with limited educational backgrounds still face challenges regarding these indicators. In terms of application, the program is running smoothly, with managers implementing a layered burial system, which is one of the best approaches currently in use. Meanwhile, the satisfaction experienced by the community is satisfactory based on compliance with applicable regulations, routine activities such as management, supervision, and maintenance of all TPU environments, as well as the performance of staff, which are all running smoothly.